The Impact of Government Debt on Economic Growth - Khac Lich, Hoang; Tu, Duong Cam (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 1, 2018)
This paper aims to examine the effects of public debt on economic growth by using a regression method of a fixed effect model with the data of 58 developed countries (high-income countries) and developing countries (low and medium income countries). The analysis shows that public debt (both in terms of scale and rate of increase), inflation, government spending and unemployment are negatively associated with economic growth. A reasonable expenditure plan (in this case, consumption expenditure) can control the impact of public debt on economic growth. More particularly, public debt has a positive impact on economic growth if consumption expenditure is larger than 14-16% of the GDP. Other factors such as TFP (Total-Factor Productivity), trade and public investment can stimulate growth in the observed sample. Interestingly, for high-income countries, economic growth rate in Assembly-elected President countries is higher than that in the Presidential countries.